Effects of wealth on nutritional status of pre-school children in Bangladesh - Kamal, S. M. Mostafa; Abdul Manaf, Rosliza; I., Md Aynul (Nutrition Society of Malaysia, 2010)
This paper explores the relationship between household wealth and nutritional status of pre-school children in Bangladesh using the nationally representative 2007 Bangladesh Demographic and Health Survey data. Chronic malnutrition was measured by z -score of height-for-age and the effect of household wealth on adverse childhood growth rate was assessed by multivariate logistic regression analyses. Overall, 43% of the children were stunted. The multivariate binary logistic regression analysis yielded significantly increased risk of stunting among the poorest (OR=2.26, 95% CI=1.77-2.89) as compared to the richest. The multivariate multinomial logistic regression produced elevated risk of moderate stunting (OR=1.98, 95% CI=1.50-2.61) and severe stunting (OR=2.88, 95% CI=2.00- 4.14) of children in the poorest category compared to their richest counterparts. Children’s age, duration of breastfeeding, mother’s education, body mass index, mother’s working status and place of region were also identified as important determinants of children’s nutritional status. The findings suggest that apart from poverty reduction, maternal education, and strengthening of child and maternal health care services are important to improve health and nutritional status of the children.